Serum metabolomics analysis of patients with polycystic ovary syndrome by mass spectrometry. Issue 3 (24th January 2019) - Jia, Chunshu; Xu, Hongmei; Xu, Ying; Xu, Ying; Shi, Qingyang
Abstract : Polycystic ovary syndrome (PCOS) is a set of symptoms caused by elevated androgens (male hormones) in females. PCOS is the most common endocrine disorder among women between 18 and 44 years. Currently, the pathogenesis of PCOS remains unclear. Liquid chromatography–mass spectrometry (LC/MS)‐based metabolomics is becoming more and more useful for medical research, especially in revealing the mechanism of the disease. The aim of this study was to investigate the difference of serum metabolic profiles in patients with PCOS and healthy control to better understand the mechanism of this disease. Ten patients with PCOS and 10 healthy people were recruited for this study. The serum samples were collected for LC/MS analysis. Multivariate statistical analysis was performed to discover and identify the potential biomarkers. Six biomarkers were found and identified. The biomarkers belonged to different metabolic pathway including lipid metabolism, carnitine metabolism, androgen metabolism, and bile acid metabolism. Those biomarkers also played different roles in disease progression. Metabolomics is a powerful tool used in research of the mechanism involved in this disease to provide useful information for better understanding of PCOS. Abstract : Liquid chromatography–mass spectrometry‐based metabolomics approach was used to investigate the metabolic changes between patients with polycystic ovary syndrome (PCOS) and healthy people. The aim of this study is to find useful biomarkers for PCOS and explore their changes in the biological pathways.